Implementasi Manajemen Pengetahuan di Lingkungan MI Nurul Huda 2 Kota Mojokerto - Ahmad Alfin Khusaini (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2022)
Indonesia's Human Development Index (HDI) belongs to the lower middle class in Southeast Asia, marked by the slowing growth of HDI, so that all elements of society are required to improve their skills and competencies. One way is through the field of education, through knowledge management in an educational institution that aims to improve the competence of the teacher council, MI Nurul Huda 2 Mojokerto City is one of the educational institutions that links the role of knowledge management as a step to improve organizational performance, through the implementation of the KKG (Group Group). Teacher Work) together with the Sister School namely MI Muslimat NU, Pucang, Sidoarjo they collaborated in creating learning innovations, which were then disseminated by KKG participants to all teachers in the educational institution, but in its implementation it was inseparable from obstacles, ranging from the lack of attendance, lack of enthusiasm and lack of enthusiasm for teachers, that's what happened, but all can be overcome by giving rewards for those who are active in activities. while there is also punishment (coaching) for those who are not active in activities, all of which are aimed at achieving the mission and goals of the organization, and the implementation of knowledge management is going well with the result of local wisdom.